Fatal oral anticoagulant‐related intracranial hemorrhage: a systematic review and meta‐analysis. (21st July 2018) - Katsanos, A. H.; Schellinger, P. D.; Köhrmann, M.; Filippatou, A.; Gurol, M. E.; Caso, V.; Paciaroni, M.; Perren, F.; Alexandrov, A. V.; Tsivgoulis, G.
Abstract : Background and purpose: Intracranial hemorrhage (ICH) is the most feared complication in patients treated with oral anticoagulants due to non‐valvular atrial fibrillation. Non‐vitamin K oral anticoagulants (NOACs) reduce the risk of ICH compared with vitamin K antagonists (VKAs). We performed a systematic review and meta‐analysis to evaluate the risk of fatal NOAC‐related ICH compared with VKA‐related ICH. Methods: We calculated the corresponding risk ratios (RRs) in each included study to express the relative risk of fatal ICH amongst all patients receiving oral anticoagulation with either NOACs or VKAs. We additionally evaluated the mortality rates in NOAC‐related ICH in patients treated with and without NOAC‐specific reversal agents (idarucizumab and factor Xa inhibitors antidote). Case fatality was evaluated at 30–90 days following symptom onset. Results: Our literature search identified six eligible studies (four randomized controlled trials and two open‐label trials of NOAC‐specific reversal agents). In pairwise analyses, NOACs were found to have a lower risk of fatal ICH compared with VKAs [RR, 0.46; 95% confidence interval (CI), 0.36–0.58] with no heterogeneity ( I 2 = 0%) across included randomized controlled trials. However, the case fatality rate was similar in NOAC‐related and VKA‐related (RR, 1.00; 95% CI, 0.84–1.19) ICH with no evidence of heterogeneity ( I 2 = 0%). In the indirect analysis, the case fatality rate of NOAC‐related ICH in patients treated with specific reversal agents was lower compared with the remainder of the patients [17% (95% CI, 11–24%) vs. 41% (95% CI, 34–49%); P < 0.001]. Conclusions: Non‐vitamin K oral anticoagulants halve the risk of fatal ICH in patients with non‐valvular atrial fibrillation compared with VKAs, whereas indirect comparisons indicate that NOAC‐specific reversal agents may be associated with a lower case fatality rate in NOAC‐related ICH.